Heterocycles from double-functionalized arenes : transition metal catalyzed coupling reactions - Wu, Xiao-Feng; Beller, Matthias (Cambridge : Royal Society Of Chemistry, 2015)
The efficient synthesis of heterocycles has become one of the main branches of organic chemistry due to their use in the synthesis of natural products and pharmaceuticals. Current synthetic strategies based on C-H activation methodologies are met with many problems like harsh reaction conditions and low reaction efficiency. Double functionalized chemicals offer a perfect alternative for the synthesis of heterocycles. This book starts with a short discussion on the imporatance of heterocycles and a brief introduction on the preparation of double-functionalized arenes. Specific chapters then look at five-membered heterocycles synthesis, six-membered heterocycles synthesis and macroheterocycles synthesis.
Includes bibliographical references and index.
Keywords: Heterocyclic compounds -- Synthesis; Aromatic compounds